1999
DOI: 10.1038/sj.hdy.6884840
|View full text |Cite
|
Sign up to set email alerts
|

Genomic coalescence in a population of Laxmannia sessiliflora (Angiospermae, Anthericaceae): an association of lethal polymorphism, self-pollination and chromosome number reduction

Abstract: A population of Laxmannia R. Br. (Angiospermae, Anthericaceae) near Collie, Western Australia, combines the taxonomically significant sessile inflorescences of L. sessiliflora Dcne. (n = 4) and the derived breeding system of L. ramosa Lindl. (n = 4). It exhibits a polymorphism for seed‐aborting lethal equivalents, significant levels of self‐pollination and a chromosome polymorphism in which a haploid genome with n = 3 is most frequent. Allozyme analysis indicates that the population is either of hybrid origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The power of this approach to help unravel evolutionary processes at the population level has been demonstrated for taxa of the Southwest Australian Floristic Region (e.g. James 1992James , 2000James et al 1999;Bussell et al 2002;Coates et al 2003;Watanabe et al 2006).…”
Section: Prolonged Speciation At the Margins (Semiarid Cradle Hypothementioning
confidence: 98%
See 1 more Smart Citation
“…The power of this approach to help unravel evolutionary processes at the population level has been demonstrated for taxa of the Southwest Australian Floristic Region (e.g. James 1992James , 2000James et al 1999;Bussell et al 2002;Coates et al 2003;Watanabe et al 2006).…”
Section: Prolonged Speciation At the Margins (Semiarid Cradle Hypothementioning
confidence: 98%
“…Cowling et al 2009; van der Niet and Johnson 2009), OCBIL theory proposes a more complex interplay of contributing causes, varying in importance from taxon to taxon, but sufficiently tractable experimentally to enable falsification of competing hypotheses in any given case (e.g. James et al 1999;Bussell et al 2002;Yates et al 2007a). Thus, seven pertinent predictions may be derived from OCBIL theory (Table 4).…”
Section: Ocbil Theorymentioning
confidence: 98%
“…Cytological mechanisms, such as genome multiplication (polyploidy) and chromosomal rearrangements leading to an increase or decrease of chromosome number (dysploidy), have greatly amplified plant diversity. Such alterations have been documented in numerous plant groups of continental regions (Grant, 1981;James et al, 1999), but few dysploid species have been reported for the Mediterranean flora (Castro & Rosselló, 2005;Vallès et al, 2005).…”
Section: Introductionmentioning
confidence: 99%